Perspektif Hukum dalam Peningkatan Ekonomi Masyarakat melalui Usaha Perkoperasian di Indonesia - Hamdan Azhar Siregar (Fakultas Hukum Universitas Kristen Indonesia, 2016)
Development of cooperatives of small and medium-sized enterprises, has become an integral part of national economic development. The presence of cooperative small and medium enterprises start since its establishment until now a a pillarnational economy, it is also reinforced in UUD1945, Article 33, however, if observed the presence and contribution can not be equated with other forms of business such as private companies and SOEs and have not been able to compete in the global market. As time goes by and the dynamic changes in all fields, the law must be able to anticipate these changes, in this case the law should not be left behind with the changes, and may be in line withdevelopment it, otherwise the development and role of law in economic development is not running optimally , Therefore, the law and the economy should be run in parallel and the law is also needed as a social control to avoid collisions with one another. Legal perspective of the running of the economy and increasing economic competitivenesscommunity, especially cooperatives, legal development is carried out through the renewal of legal materials such as the Law on Cooperatives in order to anticipate and competitive flow of globalization, particularly the economic field, but with due regard pluralistic society prevailing legal order and in an attempt to increase certainty and legal protection, law enforcement and human rights (HAM), legal awareness and legal services based on justice and truth, order and prosperity, in the framework of the implementation of state increasingly orderly, organized, smoothly, and globally competitive. Kata Kunci: Perspektif hukum dalam peningkatan Koperasi.